Unravelling the nucleophilicity of buten tides for 1,6-conjugate addition to p-quinone methides: a direct access to diversely substituted butenolide-derived diarylmethanes - Sharma, Brijesh M.; Shinde, Dinesh R.; Jain, Ruchi; Begari, Eeshwaraiah; Satbhaiya, Shruti; Gonnade, Rajesh G.; Kumar, Pradeep (Organic Letters, 2018)
A Lewis acid catalyzed regioselective C-C bond is constructed through beta-addition of deconjugated butenolides with p-quinone methides in a 1,6-conjugate addition manner. Interestingly, Lewis acid catalyzed vinylogous Mukaiyama-Michael reaction of silyloxyfurans with p-QMs proceeds selectively through the alpha or gamma position exclusively. The reaction is mild with broad substrate scope, thus allowing easy access to a wide range of bis-arylated alpha-/beta-/gamma-substituted butenolides.

Tf2NH catalyzed 1,6-conjugate addition of 2-hydroxy-p-quinone methides with -functionalized ketones: access to 2,3,4,9-Tetrahydro-1H-xanthenones and 4H-Chromene Derivatives - Satbhaiya, Shruti; Khonde, Nilesh S.; Rathod, Jayant; Gonnade, Rajesh; Kumar, Pradeep (European Journal of Organic Chemistry, 2019)
A Bronsted acid catalyzed tandem 1,6-conjugate sequential cycloaddition reaction using 2-hydroxy-p-quinone methides and -functionalized ketones is reported. The method allows xanthenones and chromenes to be accessed in moderate to excellent yield with broad substrate scope, which could be further functionalized to give a versatile set of products.
Keywords: -Functionalized ketone; 1; 6-Conjugated addition; Bronsted acid; Chromenes; Xanthenones